Sustainability of the family ownership in a family business via inheritance: An Appraisal with special reference to the Malaysian law. - Mohd Salim, Wan Noraini; Abdul Ghadas, Zuhairah Ariff (INSI Publications, 2012)
According to Amran and Che Ahmad (2010), family succession attributes influence the firm’s performance and the family ownership is positively related with the firm’s performance. The writers also observed that families are motivated to work efficiently when they hold more shares in the business. Furthermore, the results reveal that successors-managed firms have better firm performance than founder-managed firms. The findings provide evidence that Malaysian family firms do plan for their successions. However, in absence of the succession plan, it is observed that the family business structure could still maintained by the application of the law of inheritance. This paper intends to highlight how the inheritance laws play its role in maintaining the family ownership in family business. The scope of discussion in this paper is focus on family businesses in Malaysia and the conventional and Islamic laws of inheritance which are applicable in Malaysia. Research methodologies applied in this paper are statutory and doctrinal analysis.